The Degree of Educational Supervisors' Commitment to the Ethics of Classroom Visits as Perceived by Kuwaiti Teachers - Salem S. Alhajeri; Meznah S. Alazmi; Anwar F. Alharshani (Sultan Qaboos University, 2018)
This study aimed to identify teachers' perceptions of the extent to which educational supervisors are committed to the ethics of classroom visits in public schools in the State of Kuwait. The study sample consisted of 682 teachers who were selected by random cluster sampling. To achieve the objectives of the study, the researchers used a questionnaire that comprised 42 items divided into three dimensions (before classroom visit, during classroom visits, and after classroom visits). The results of the study revealed that the degree of adherence to the ethics of classroom visits ranged from very high to high. There were statistically significant differences in the domain of before classroom visits due to gender, nationality and specialization However, there were no differences due to years in service.The study recommended a change from the culture of unannounced to announced classroom visits.